THE JUDICIAL REFORM, DUE PROCESS OF LAW AND MARKET DEMOCRACY: THE WORLD BANK AS FORMANT AND LEGAL TRANSPLANTS EXOGENOUS TO BRAZILIAN CIVIL PROCEDURE - Leitão, Roberto Guilherme; Leitão, Rômulo (Revista Inclusiones, 2021)
The article attempts to analyze the existing relational link between the reform of the judiciary, due process (due process of law) and market democracy. For this, it has to face the interference and conditions imposed by the World Bank, in order to reform the institutional framework, constitutional and procedural Brazilian. And yet, it seeks to scrutinize the consequences facing the judicial structure and the Brazilian civil procedure. Furthermore, and as consectário these reforms, there being studied the spread of "common law" as formant and legal transplants (legal transplants) exogenous to the Brazilian civil procedure. Conceiving the existing tension between the structure of the judiciary shaped in the Federal Constitution and the result of the Judicial Reform (Constitutional Amendment nº 45). To this aim, will be made the following considerations 1) Understand the framework of this investigation, ie procedural changes within the judicial reform, the theory of legal transplants and School of law and development; 2) Develop the relationship between the identity of the civilian school in the Brazilian civil procedure (civil law) and the changes initiated by the common law school; 3) What is the interference of the World Bank (School of law and development), and in consequence of the common law and due process in the Brazilian procedural law; 4) How the Brazilian procedural model, constitutionally enshrined, has incorporated the reports of "Repport" from the World Bank? ; 5) What is the density of democratic procedural reforms on the relationship of "rule of law" and the developmental matrix of World Bank?